Hazardous Alcohol Use and Insomnia in women and men: Insights from the population-based Tromsø Study 2015-2016. - Husberg, Vendela (UiT Norges arktiske universitet, 2021)
Background and aims: Hazardous alcohol use is known to be comorbid with insomnia. The aim of this study was to estimate the prevalence of co-occurring hazardous alcohol use and insomnia symptoms, and the odds of insomnia among women and men with a hazardous alcohol use, using logistic regression and covariate-adjusted moderation analysis. Design setting: Cross-sectional data from the seventh survey of the Norwegian population-based Tromsø Study 2015-2016 (participation 65%). Participants:The sample included 17 381 women and men 40-96 years. Measurements:Hazardous alcohol was defined by the Alcohol Use Disorder Identification Test and insomnia by the Bergen Insomnia Scale. Covariates included socio-demographics, shift work, somatic conditions disease and mental distress (defined by Hopkins Symptom Check List). Findings: Insomnia was more prevalent among participants with hazardous alcohol use (21.2%) than without (17.9%). Hazardous alcohol users had higher odds of insomnia (odds ratio=1.69, 95% confidence interval 1.38, 2.06), but the effect was non-significant after adjustment for mental distress. In moderation analyses the higher odds of insomnia among hazardous alcohol users was present only at low and mean levels of mental distress, and not among participants reporting high levels of mental distress. Conclusion: Insomnia was more prevalent among women and men reporting hazardous alcohol use. Mental distress may play an important role in the association between hazardous alcohol use and insomnia.